Exploring cognitive Landscapes: Longitudinal Dynamics of left insula gliomas using neuropsychological inquiry, fMRI, and intra-resection real time neuropsychological testing - Elisa Cargnelutti; Marta Maieron; Serena D’Agostini; Tamara Ius; Miran Skrap; Barbara Tomasino (NeuroImage: Clinical)
We explored the functional outcome following awake surgery and Real-Time Neuropsychological Testing (RTNT) in the left insula. We carried out a longitudinal investigation by comparing the patients’ language profile, and, in particular, the object-naming skills and the associated fMRI network, of pre-surgery and follow-up (i.e., a few months after surgery) in a group of 23 patients harboring a left-sided low grade glioma centered to the insulo-temporal area.Tumor resection, performed while continuously monitoring patients’ performance by RNTN, was high (median = 92 %). From the neuropsychological viewpoint, almost all patients displayed preserved naming and language skills in general, both before surgery and at follow-up, when they recovered from a transient impairment recorded immediately after surgery. From the functional imaging viewpoint, the naming networks of the two assessment times were almost equivalent, with non-parametric analyses showing brain remodeling involving perilesional areas preoperatively and the contralesional, healthy, insula at follow-up.We discussed the anatomo-functional mechanisms that contributed to the preservation of the functional and cognitive pattern as observed in this longitudinal study, with a particular focus on the promising plasticity potential of the left insular area. In particular, we commented that, at least in our patient series and by applying an optimized surgical procedure, surgery in the insula was safe and generally contributed to the preservation of the language functions.